Logística reversa de medicamentos domiciliares vencidos, em desuso e suas embalagens: perspectivas para a implementação no município de São Carlos/SP - Pereira, Alana (Universidade Federal de São Carlos, 2020)
The disposal of post-consumer drugs has gained relevance and increasing complexity, mainly due to the significant increase in drug consumption in recent years, as opposed to the low efficiency of drug removal from water resources in traditional treatment systems. The municipality under study has Municipal Law No. 17.647 of 2015 - which instigated this research - and, in the approval phase, the Municipal Plan for Integrated Solid Waste Management (MPISWM). During the development of this study, the reverse logistics system (RLS) of expired or unused household medicines (EUHM) and their packaging was instituted, nationwide, by Federal Decree No. 10,388 of 2020. The main objective was to analyze the status of the reverse logistic of EUHM and its packaging in the municipality of São Carlos/SP. The methodology consisted of an analysis of theoretical references and legislation on the topic; physical characterization of household waste; and application of questionnaires with those responsible for pharmacies and drugstores, residents and public actors. It was possible to identify that the EUHM and its packaging found in the municipal landfill include, for the most part, analgesics and anti-inflammatories (15%), antihypertensives (10%), analgesics and antipyretics, antibiotics, antidepressants, replacement drugs hormonal, among others. Of the 87 pharmacies and drugstores in the municipality, 38 establishments (44%) participated, most do not receive EUHM (61%) and, among those who do (39%), there is no standardization of the procedures adopted. Regarding the citizens, a random sampling by households was carried out, resulting in the participation of 388 citizens. The statistical model used allowed to infer that the variables that interfere in the form of disposal by citizens of São Carlos are education and knowledge of Municipal Law No. 17,647 of 2015. About public actions, it was possible to identify that the municipality does not have an RLS for EUHM and its packaging; does not articulate programs in the area of waste management of health services (HS); and does not provide clarification to the population on this topic. Therefore, it is recommended to adopt management measures and public policies to change the scenario presented and strategies to reduce the generation of EUHM and its packaging, in addition to investment in education, promotion of educational campaigns and dissemination of laws and collectors of EUHM and its packaging in the municipality.
Reverse logistics of expired and unused household drugs and their packaging: perspectives for implementation in the city of São Carlos/SP
Keywords: Sistemas de Logística Reversa; Descarte de medicamentos; Embalagens de medicamentos; Resíduos de serviços de saúde; Gestão de resíduos; Reverse Logistics Systems; Drug disposal; Medicine packaging; Waste management; Health service waste; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL